Case report: Fourth branchial cleft cyst: a case of acute suppurative thyroiditis - Caseiro Alves, M. Eduarda; Nunes, Ana; Galhardo, Júlia (Frontiers in Pediatrics, 2023)
This case report presents a 4 year-old-female patient with a neck mass who was diagnosed with an infected fourth branchial cleft cyst with left thyroid lobe involvement through fistulation. The case emphasizes the importance of considering uncommon etiologies, such as congenital anomalies, as a differential diagnosis when evaluating pediatric neck masses. The patient was prescribed broad-spectrum antibiotics, which led to the regression of the mass and inflammatory signs. Close follow-up in endocrinology and otorhinolaryngology appointments was maintained, and after 7 months, hypoplasia of the left lobe was observed. Thyroid function was reevaluated, and after two years, no recurrences were noted. The case highlights the significance of a comprehensive examination and assessment of corresponding clinical features, which can significantly reduce the rate of misdiagnoses and achieve an individualized diagnosis.